CLASSIFICATION OF OBJECTS OF INCOMPLETE CONSTRUCTION AS A TOOL OF VALUE MANAGEMENT METHODOLOGY - Elena Yu. Morozova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article provides the notion of the object of incomplete construction with regard to specific features of real estate and property complexes. The author gives examples of well-known objects of incomplete construction in Russian and abroad. Existing classifications of objects of incomplete construction and property complexes were analyzed and the structure of objects of incomplete construction was identified taking into account assessment principles. A new classification of objects of incomplete construction was proposed with the aim of value management. Types of objects were described. According to the classification the author defines principles of value management for objects of incomplete construction.